Physical and chemical of soil properties area coffee in Several Banjar Villages, Bangka Regency - Ratna Santi; Nyayu Siti Khodijah; Siti Cahyani (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2024)
Coffee plants are one of the plantations commodities in Bangka district bisides from pepper and rubber. The area of coffee plantations in Bangka district was 302,879 Ha with total production from 39.05 Ha of 3 tons. The distribution of community coffee plantations was mainly in the villages Riding Panjang, Deniang, Petaling Banjar, Air with coffee production fluctuating every year. Community managed coffee plantations contain some mature plants and some immature plants. Plant growth and production are influenced by soil and climate conditions. The research aimed to determine the physical and chemical characteristics of coffee plants in four Villages of Bangka Regency. The research method uses survey observation measurements in the field and sample analysis in the laboratory. Soil samples were taken using the diagonal random method. Soil samples were taken at each of the 4 location reseach. Soil chemical properties resulting from analysis at the ICBB Bogor laboratory include pH and soil nutrient availability. Soil biophysical observations carried out include soil color, texture, bulk density, soil porosity, drainage,effective rooting depth. Based on the chemical and physical properties analyzed, the soil condition in the coffee planting area was classified as sour with nutriens availability, low cation exchange capacity and a sandy clay loam texture with low porosity.